(untitled) (Mongolian Journal of Humanities and Social Sciences, 2024)
This article examines the meanings, transformations, and extensions of nouns denoting the color “brown” in the Mongolian language, with a specific focus on semantic and cognitive approaches. The analysis identifies six distinct semantic categories, or semantemes, derived from the color term “brown”: “color representation, poverty, simplicity, tenderness, warmth, calmness, and darkness.” Notably, the semantic map associated with “brown” in Mongolian differs significantly from that of other linguistic and cultural groups. The extension of meaning associated with the color “brown” is influenced by its psychological impact on human perception, as well as by its symbolic relationship with “blue” and “brown” in representing vertical spatial orientation in Mongolian culture. This symbolic association serves as a foundation for constructing complex semantic units within the color lexicon, particularly in expressions describing facial color. These semantic extensions go beyond the basic lexical meaning of words, encompassing cultural connotations, values, and symbols embedded in the language. The alternative semantemes or derived meanings, when combined into a complex unit, acquire a metaphorical quality that reflects cognitive processes and embodies cultural thought patterns. The shift in meaning is closely linked to the development and evolution of vocabulary, shaped by etymology, national symbols, and cultural nuances. This article argues that constructing semantic maps for vocabulary units, and investigating semantic shifts and extensions based on these units, are essential for advancing research in semantics and comparative linguistic studies across languages. Монгол хэлний өнгөний нэрээр илрэх утгын өргөслийг судлах нь (Бор өнгөний нэрийн жишээн дээр) Хураангуй: Тус өгүүлэлд монгол хэлний “бор” өнгөний нэр бүхий нийлмэл нэгжээр илрэх утга, утгын хувьсал, өргөсөл, утгын хүрээг утга зүй, танин мэдэхүйн үүднээс авч үзлээ. “Бор” өнгөний нэрээс улбаатай утгын өөрчлөлтийг авч үзэхэд “өнгө заах, ядуу дорой, эгэл энгийн, энхрий дотно, дулаан тайван, харанхуй бүрэнхий” 6 салаа утгыг үүсгэж байгаа бөгөөд 3156 хэлийг багтаасан утгын хүрээтэй (semantic map) харьцуулж үзэхэд “бор” өнгөний нэрээс үүссэн утгын хүрээ нь бусад хэл соёлт ард түмнээс ялгаатай байна. Мөн түүнчлэн утгын өргөсөл нь бор өнгөний хүний сэтгэл зүйд нөлөөлөх нөлөөлөл болон хүн төрөлхтний орон зайн босоо чигийн төлөөлүүлсэн “хөх-тэнгэр”, “бор-газар” гэх өнгөний бэлгэдэлтэй холбоотой газар хөрсний өнгө, мөн монгол хүний царайны өнгөнөөс улбаатай нийлмэл нэгж үүсэх суурь болж, үгийн сангийн утгаас гадна хэлний соёл хэрэглээ, хэлний үнэлэмж, бэлгэдэлтэй холбогдож, утгалбарын хувилбар буюу салаа утгууд нь нийлмэл нэгжээр илрэхдээ танихуйн зүйрлэлийн шинжтэй, соёл сэтгэлгээний онцлогийг тээж бүтжээ. Эдгээр нийлмэл нэгжээр илрэх утга нь үгийн сангийн утгаас гадна соёлын үнэт зүйл, үнэлэмж, бэлгэдлийн утгыг багтааж, соёл хэрэглээний талын тодруулан, үгийн утга түүгээр илрэх үнэлэмж, соёлын асуудлыг хөндсөнөөрөө үгийн сангийн утга судлал, үгийн утгын соёл танихуйн асуудал, угсаатны зүйн судалгаанд ч холбоотой. Нөгөө талаас тухайн ард түмний түүх, ёс заншил, амьдралын тогтсон хэв маяг, сэтгэлгээний онцлогийг хэлээр дамжуулан сурдаг тул монгол хэл сурах, заах асуудалд тодорхой хувь нэмэр оруулахаас гадна соёлыг хэлээр дамжуулан таниулах, хамгаалахад чухал ач холбогдолтой. Түлхүүр үг: бор, өнгөний нэр, утгын өөрчлөлт, өргөсөл, утгын сүлжээ (хүрээ), зүйрлэл